Potensi Beta-Hydroxybutyrate (BHB) dalam Penanganan Diabetes Tipe 2 dan Risiko Ketoasidosis pada Pasien Diabetes - Balapadang, Rachel Noveriachristie; Sudarjat, Hadi (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2024)
Diabetes mellitus (DM) is a metabolic disease with an increasing prevalence every year, especially type 2 DM. Before insulin as a DM therapy, the ketogenic diet was known as the main nonpharmacological therapy, which is a high-fat, adequate-protein, and low-carbohydrate intake diet. A ketogenic diet causes the ketogenesis process and produces ketone bodies, one of which is beta-hydroxybutyrate (BHB) which has various therapeutic effects such as lowering blood sugar levels. This study is a narrative review compiled by searching the literature on Google Scholar and PubMed databases with keywords related to the research topic. Bibliometric analysis was also carried out with VOSviewer software to determine the keywords relevant to the research topic. The results of the reviews that have been carried out show that BHB has the potential as a therapeutic agent in patients with DM2 with various mechanisms of action in lowering blood sugar levels including increased insulin secretion, suppression of lipolysis, and decreased Ala release. BHB as a supplement has been widely studied for its therapeutic effects but it is necessary to pay attention to the side effects that can occur such as ketoacidosis.